2016
DOI: 10.1073/pnas.1613199114
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid signaling is controlled by a BRANCHED1/HD-ZIP I cascade in Arabidopsis axillary buds

Abstract: Shoot-branching patterns determine key aspects of plant life and are important targets for crop breeding. However, we are still largely ignorant of the genetic networks controlling locally the most important decision during branch development: whether the axillary bud, or branch primordium, grows out to give a lateral shoot or remains dormant. Here we show that, inside the buds, the TEOSINTE BRANCHED1, CYCLOIDEA, PCF (TCP) transcription factor BRANCHED1 (BRC1) binds to and positively regulates the transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
269
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(291 citation statements)
references
References 33 publications
16
269
1
5
Order By: Relevance
“…gt1 was also found to be genetically downstream of tb1 (52), and is likely another TB1 target. In addition, recent work in Arabidopsis showed that gt1 homologs are directly targeted by BRC1, and regulate ABA levels and signaling (53). Both gt1 and tru1 independently control a subset of phenotypes seen in tb1, where gt1 represses tiller number at ground level, while tru1 represses axillary bud growth aboveground, without affecting tillering (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…gt1 was also found to be genetically downstream of tb1 (52), and is likely another TB1 target. In addition, recent work in Arabidopsis showed that gt1 homologs are directly targeted by BRC1, and regulate ABA levels and signaling (53). Both gt1 and tru1 independently control a subset of phenotypes seen in tb1, where gt1 represses tiller number at ground level, while tru1 represses axillary bud growth aboveground, without affecting tillering (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…TB1(monocots)/BRC1(dicots) is a TCP transcription factor mainly expressed in dormant axillary meristems inhibiting their outgrowth Takeda et al 2003;Hubbard et al 2002). Given the role of TB1/BRC1 as integrator of multiple signals involved in bud outgrowth, mayor attention has been given to this gene in recent years (Martín-Trillo et al 2011;Nicolas et al 2015;Braun et al 2012;González-Grandío et al 2017).…”
Section: Ramosus (Rms) In Pea Decreased Apical Dominance (Dad) In Pementioning
confidence: 99%
“…However, the buds that are initiated when the shoot apical meristem (SAM) of their mother has transitioned into the reproductive state ('A and B' buds in tulip), are able to skip this kind of dormancy (Chapter 4 and (Rees 1968)). This particular dormancy is known as paradormancy and imposed by apical dominance (Lang et al 1987 (Yao and Finlayson 2015;González-Grandío et al 2017;GomezRoldan et al 2008;Liang et al 2010;Pasare et al 2013;González-Grandío and Cubas 2014;Wu et al 2015;Hartmann et al 2011). …”
Section: What Can We Learn From Axillary Bud Outgrowth In Tulip?mentioning
confidence: 99%
See 1 more Smart Citation
“…The current knowledge about HD‐Zip I TFs was acquired by different techniques including sequencing, next generation sequencing, expression patterns and characterization of overexpressing and/or mutant plants, among others . This knowledge helped to understand the regulation of gene expression in plants as well as to discover signal transduction pathways.…”
Section: Considerations About the Tools Applied To Study Hd‐zip I Tfsmentioning
confidence: 99%